The effect of the proactive guide strategy on reading comprehension and visual thinking among first-grade intermediate students (Journal of the College of Basic Education, 2023)
The current research aims to know the effect of the visual feedback strategy on reading comprehension and visual thinking for first-grade intermediate students. ) located in the Shubar neighborhood, the center of Babil Governorate, and in the same way he chose Division (A) to represent the control group of thirty-five students, and Division (C) to represent the experimental group of thirty-seven students, who prepared daily plans for teaching the two research groups and two presentations Among them, a group of experts and specialists were required to know their validity and suitability for first-grade intermediate students. The researcher also prepared two research tools. They prepared a reading comprehension test consisting of two questions, the first consisting of sixteen objective paragraphs, the type of multiple choice, and the second consisting of eight paragraphs of the essay paragraphs. , preparing a visual thinking test consisting of five sections and twenty-five test items of the multiple-choice type, for each section five paragraphs. After analyzing the results statistically, the researchers concluded: The students of the experimental group that studied the reading material by using the pictorial notes strategy outperformed the students of the control group that studied the same material in the traditional way in the reading comprehension test and the visual thinking test. In light of these results, the researchers recommended a set of recommendations, including the need to use The dummy notes strategy in teaching reading because of its positive impact on improving students’ learning, and training Arabic language teachers in the middle school on modern strategies in teaching to develop the ability to understand reading, including the pictorial notes strategy. The researchers suggested conducting a similar study to the current study to develop reading comprehension in Other stages of study Conducting a study to identify the effect of the picture notes strategy in improving the teaching of other branches of the Arabic language such as grammar or rhetoric.